PENGEMBANGAN SISTEM MONITORING PASIEN OLEH DOKTER PADA RSUD BANGIL BERBASIS WEB - Kurniawan Wahyu Haryanto; Mahadi Setiawan (SPIRIT, 2022)
Abstract : Bangil Regional General Hospital is one of the hospitals in Pasuruan Regency. RSUD Bangil was inaugurated in 1981. The Bangil General Hospital is a hospital owned by the local government of Pasuruan Regency, which historically started as a puskesmas which along with its development had difficulty accommodating more and more patients. In this study, the problems faced by health workers, especially doctors, were when monitoring their patients or when they saw the patient's current condition, while at the same time doctors were not always there, but some were on holiday, some were out of town. Doctors find it difficult to get information, especially regarding the patient's current condition at that time. Not to mention that there is a critical patient and requires instructions for administering medication or other doses, the purpose of this study is to assist doctors in monitoring patients by using the help of a website. With this website-based application, it is hoped that it can facilitate the work of doctors in monitoring patients and provide direct instructions so that services are better and do not need to come repeatedly to see and give drug instructions while out of town or on holidays.